Relationship between Mathematics Diagnostic Test and Mathematics Final Assessment Among Pre-University Students Based on Gender - Farah Liyana, Azizan; Tan, George Geok Shim (Human Resource Management Academic Research Society (HRMARS), 2021)
Diagnostic testing is considered as an important device that can be used by educators to identify students' strong and weak points in Mathematics subjects as it is often used as a preliminary evaluation of basic Mathematics skills of students. Educators must be able to detect the students' mathematical capacity earlier before delivering new content to them. This article purposes are to identify the achievement of pre-university students in Mathematics diagnostic test and Mathematics final assessment based on their gender, the differences between the gender of the students with their achievement in Mathematics diagnostic test, and the correlation between the students' Mathematics diagnostic test and their achievement in pre-university Mathematics final assessment. The findings demonstrated that students of both genders, who accomplished good results in their Mathematics diagnostic test, did similarly good in their final assessment. Also, students who carried out badly in their Mathematics diagnostic test did poorly in their final assessment. From this diagnostic result, it facilitates the educator to provide the students with the best teaching method and material required.